Influence of Sintering Aid on the Translucency of Spark Plasma‐Sintered Silicon Nitride Ceramics. Issue 8 (6th May 2013) - Yang, Wenwu; Hojo, Junichi; Enomoto, Naoya; Tanaka, Yumi; Inada, Miki; Chan, H.
<x xml:space="preserve">Abstract</x> Single additives (Y2O3, MgO, and Al2O3) were used as sintering aid of Si3N4. The density, crystal phase, microstructure, transmittance, hardness, and fracture toughness of sintered Si3N4 were investigated. Highly densified sintered bodies were obtained in single Y2O3 and MgO systems, but not in single Al2O3 system. The XRD results indicated that sintered bodies were composed of β‐Si3N4. The SEM images showed that all the sintered bodies had a fine‐grained microstructure with an average diameter of 0.29–0.37 μm. The thickness of grain boundary was changed with additive content. The transmittance (T) and the wavelength (λ) followed the relationship of T∝ exp(−λ−2.3) due to the light scattering. The transmittance was mainly influenced by the refractive index of additives and the thickness of grain boundary phase. The hardness and fracture toughness of sintered ceramics were 12.6–15.5 GPa and 6.2–7.2 MPam1/2, respectively.